Intervenciones de enfermería en un paciente adulto con parálisis cerebral espástica - Navarrete Cruz, Vanessa Lilibeth (2024)
Spastic cerebral palsy is a chronic neuromotor condition, a complication that can occur from birth, development and until adulthood, causing a great impact on the motor disability and neurological damage of the person who suffers from it. This case study focused on implementing nursing processes and interventions designed to improve the patient's quality of life and the various associated disorders. To address this objective, a methodological approach based on the Nursing Care Process (PAE) was used, which included stages of assessment, diagnosis, planning, execution and evaluation. During the assessment phase, a comprehensive evaluation was carried out that covered physical, psychological and social aspects. In the physical evaluation, problems such as swallowing, muscle rigidity, and mobility difficulties were identified. The psychological evaluation revealed levels of anxiety and the social evaluation highlighted the care provided by his mother. The planning of interventions was structured into short and long-term objectives. Short-term goals included reduction of spasticity through physical therapy techniques and passive exercises, swallowing status through proper diet and eating techniques, and prevention of pressure ulcers through a regimen of regular postural changes. The long-term objectives focused on improving mobility and promoting effective communication, patient and caregiver education. The results showed significant improvements in the patient's life, from an emotional point of view and mood that improved due to psychological and social support. In conclusion, this case study demonstrates that a comprehensive and personalized approach in nursing interventions is crucial to optimize the quality of life of patients with spastic cerebral palsy, addressing both physical and emotional needs effectively.